Ritonavir analogues as a probe for deciphering the cytochrome P450 3A4 inhibitory mechanism - Sevrioukova, Irina F. (Curr Top Med Chem, 2014)
Inactivation of human drug-metabolizing cytochrome P450 3A4 (CYP3A4) could lead to serious adverse events such as drug-drug interactions and toxicity. However, when properly controlled, CYP3A4 inhibition may be beneficial as it can improve clinical efficacy of co-administered therapeutics that otherwise are quickly metabolized by CYP3A4. Currently, the CYP3A4 inhibitor ritonavir and its derivative cobicistat are prescribed to HIV patients as pharmacoenhancers. Both drugs were designed based on the chemical structure/activity relationships rather than the CYP3A4 crystal structure. To unravel the structural basis of CYP3A4 inhibition, we compared the binding modes of ritonavir and ten analogues using biochemical, mutagenesis and x-ray crystallography techniques. This review summarizes our findings on the relative contribution of the heme-ligating moiety, side chains and the terminal group of ritonavir-like molecules to the ligand binding process, and highlights strategies for a structure-guided design of CYP3A4 inactivators.